IMAGES OF THE SUBALTERN: REPRESENTATIONS OF CONTEMPORARY PORTUGUESE IDENTITY IN THE NOVELS OF VALTER HUGO MÃE - Hatton, Anneliese Felicity (2023)
This thesis is unique in two ways; it is redeploying Gramsci’s notion of the subaltern to Europe, and it is the first in the English language to examine the work of contemporary Portuguese author valter hugo mãe. It examines how valter hugo mãe is altering the literary discourse of Portuguese national identity by constructing characters that subvert generally accepted notions of portugalidade by representing aspects of subalternity, thereby contributing to the development of post-nationalist thought within Portugal. This entails a re-application of Gramscian subaltern theory to the European arena after its appropriation by postcolonial theorists, and a detailed analysis of post-national, postcolonial and identity theories within a Gramscian framework, and how these have come to inform the author’s work and what this means in terms of the cultural construction of Portuguese identity. Bakhtin’s chronotope theory deepens the analysis of subalternity as it allows for a deeper understanding of how spatio-temporal literary constructions condition narratives, thereby perpetuating both hegemonic and subaltern status. The social status of the characters within valter hugo mãe’s novels is examined through an analysis of how their personal identities represent questions surrounding collective national identity in contemporary Portugal. The existing hegemonic structure is also challenged through an analysis of the representation of Portuguese religiosity and the supernatural in the tetralogy. The imposition of a certain identity upon the characters by Portuguese society, and how their acceptance or rejection of these identities affects both themselves and society as a whole allows the author to explore how meanings of identity have changed as a result of increasing globalization and the impact this has made upon collective Portuguese identity. The four novels were published between 2004 and 2010, meaning that they truly reflect anxieties that have arisen in recent times surrounding Portuguese perceptions of itself and its global status, making a study of these hugely valuable for understanding contemporary Portuguese identity.